A PENERAPAN PSIKOEDUKASI UNTUK MENINGKATKAN PERSEPSI POSITIF TERHADAP KUALITAS KEHIDUPAN SEKOLAH PADA SISWA SMA DI JAKARTA SELATAN - Rahmah - Hastuti (Jurnal Pengabdian Kepada Masyarakat Sakai Sambayan, 2021)
High school students are in their teens who are characterized by having attitudes and behaviors capable of actively participating in social activities in the community, especially in schools. Schools that provide more support needed by adolescents to develop themselves will be positively perceived by students. Students' perceptions shown by satisfaction with school in general are known as quality of school life. This research was conducted at one private school in Jakarta which involved 113 students. Students are given psychoeducation and respond to the pre-test and post-test questionnaire. Based on the results of statistical calculations with SPSS applications programme, the results show that there is no effect of the application of psychoeducation to improve the quality of school life in students. Students' perceptions also tend to be low regarding through the quality of school life. However, female students have a more positive perception than male students about the quality of their school life.